Cyber terrorism political and economic implications - Colarik, Andrew M.; IGI eBooks; IGI Global (Hershey, Pa. : IGI Global (701 E. Chocolate Avenue, Hershey, Pennsylvania, 17033, USA), 2006)
This book is a cyber terrorism brief that outlines many of the recent terrorist activities, political objectives, and their use of cyberspace. Much of this book is dedicated to illustrating the use of the global information infrastructure by terrorists for the communication and coordination of distributed terrorist cells, the gathering of target intelligence, and the use of cyber criminal activities as a force multiplier for both physical attacks and infrastructure destabilization. This book identifies the underlying technologies of the global information infrastructure as a means for presenting how critical this emerging domain has become. It then discusses the current attack methods and lays out a series of scenarios for key industry sectors. Lastly, this book puts forward prevention and response policies for reducing cyber terrorism activities in the context of traditional information security objectives.
1. Introduction -- 2. The power of terrorism -- 3. Cyber terrorism evolution -- 4. Global information infrastructure -- 5. Current cyber attack methods -- 6. Attack scenarios -- 7. Thoughts for the future.
Includes bibliographical references (p. 163-165) and index.
Also available in print.
Mode of access: World Wide Web.
Title from PDF t.p. (viewed on June 5, 2010).
Keywords: Cyberterrorism; Computer crimes; Information superhighway -- Economic aspects; Information warfare -- Political aspects; Asymmetric warfare; Computer networks -- Security measures; Electronic books